Limits of Sequences and Functions textbook - Konev, V. V. mathematician Associate Professor of Tomsk Polytechnic University, Candidate of Physics and Mathematics 1951- (TPU Publishing House, 2020)
This textbook consists of two parts devoted to the mathematical concepts of Limits. Different formulations of limits help to understand better the unity of various approaches to this concept. The basic concepts are explained by examples and illustrated by figures. The textbook is designed for English speaking students at Tomsk Polytechnic University.